Phytoplankton phenotype plasticity induced by phosphorus starvation may play a significant role in marine microbial ecology and biogeochemistry. Issue 3 (August 2016) - Brandsma, Joost
Abstract : This article is a commentary onShemi et al., 211 : 886–898 .